How to Become a Mentalist: Reading Decisions from a Competitor’s Pupil Can Be Achieved without Training but Requires Instruction - Naber, Marnix (Public Library of Science, 2013)
Pupil dilation is implicated as a marker of decision-making as well as of cognitive and emotional processes. Here we tested whether individuals can exploit another’s pupil to their advantage. We first recorded the eyes of 3 "opponents", while they were playing a modified version of the "rock-paper-scissors" childhood game. The recorded videos served as stimuli to a second set of participants. These "players" played rock-paper-scissors against the pre-recorded opponents in a variety of conditions. When players just observed the opponents’ eyes without specific instruction their probability of winning was at chance. When informed that the time of maximum pupil dilation was indicative of the opponents’ choice, however, players raised their winning probability significantly above chance. When just watching the reconstructed area of the pupil against a gray background, players achieved similar performance, showing that players indeed exploited the pupil, rather than other facial cues. Since maximum pupil dilation was correct about the opponents’ decision only in 60% of trials (chance 33%), we finally tested whether increasing this validity to 100% would allow spontaneous learning. Indeed, when players were given no information, but the pupil was informative about the opponent’s response in all trials, players performed significantly above chance on average and half (5/10) reached significance at an individual level. Together these results suggest that people can in principle use the pupil to detect cognitive decisions in another individual, but that most people have neither explicit knowledge of the pupil’s utility nor have they learnt to use it despite a lifetime of exposure.